1982
DOI: 10.1002/cne.902120302
|View full text |Cite
|
Sign up to set email alerts
|

Retinal degeneration in the pcd cerebellar mutant mouse. I. Light microscopic and autoradiographio analysis

Abstract: The Purkinje cell degeneration (pcd) mutant mouse rapidly loses cerebellar Purkinje cells between 3 and 5 weeks after birth and slowly loses retinal photoreceptor cells during the first year of life. In the present study, the retinal degeneration in the pcd mouse was analyzed by light microscopy and autoradiography throughout the first 15 months of age. By day 25 there is an abundance of pyknotic photoreceptor nuclei and many outer segments are clearly disorganized. Thereafter, as the photoreceptor cells are l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0
9

Year Published

1986
1986
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(62 citation statements)
references
References 34 publications
3
50
0
9
Order By: Relevance
“…Using a knockout mouse model for the glycylase TTLL3, we demonstrate that changes in the levels of glycylation lead to hyperglutamylation, followed by progressive degeneration of the photoreceptors. This situation is comparable to that of the pcd mouse model, which has earlier been shown to develop retinal degeneration Blanks and Spee, 1992;LaVail et al, 1982). Our data demonstrate that both glycylation and glutamylation are enriched at the photoreceptor connecting cilium, and that they influence each other.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…Using a knockout mouse model for the glycylase TTLL3, we demonstrate that changes in the levels of glycylation lead to hyperglutamylation, followed by progressive degeneration of the photoreceptors. This situation is comparable to that of the pcd mouse model, which has earlier been shown to develop retinal degeneration Blanks and Spee, 1992;LaVail et al, 1982). Our data demonstrate that both glycylation and glutamylation are enriched at the photoreceptor connecting cilium, and that they influence each other.…”
Section: Introductionsupporting
confidence: 81%
“…Strikingly, pcd mice also show progressive degeneration of photoreceptors, which starts at P15, when the first pyknotic nuclei can be observed in photoreceptors. Between 3 and 5 weeks of age, 50% of the photoreceptors are lost, and degeneration is complete after 1 year Chang et al, 2002;LaVail et al, 1982;Mullen and LaVail, 1975).…”
Section: Glycylation Controls the Length And Functionality Of Photorementioning
confidence: 99%
“…Such patterns of hypopigmentation, due to a variety of causes including but not limited to RPE cell dropout, have been seen in fundus photographs of most of the known murine inherited retinal degenerations~Hawes et al, 1999;Chang et al, 2002;Mehalow et al, 2003;Pang et al, 2005!. As we have reported here, several studies correlate areas of RPE cell thinning with the apposing and localized loss of photoreceptor cell bodies comprising the ONL~Caley et al, 1972;Sanyal & Bal, 1973;Sanyal et al, 1980;LaVail et al, 1982LaVail et al, , 1993Blanks et al, 1982;Messer et al, 1993!. As in other photoreceptor degenerations, Müller cells fill in space left by these dying photoreceptors. Though immunocytochemistry shows that there is some upregulation of GFAP in these cells, as has been seen in other retinal degenerations~Eisenfeld et al, 1984;Lewis et al, 1994!, we , there is an increase in apoptotic profiles though they are still restricted to the inner retinal layers.…”
Section: Discussionsupporting
confidence: 67%
“…CCP1 mRNA is most highly expressed in the zebrafish brain, consistent with expression patterns of CCP1 mRNA in the mouse and with the neuronal phenotypes of the pcd mutants (11). Our study indicated a smaller eye size in CCP1 and CCP5 morphants that could be related to photoreceptor degeneration, although this does not normally occur in the pcd mouse until relatively late in development (38,39). Finally, the broad expression of CCP1 mRNA at early developmental stages but viability of morphant embryos suggests partial redundancy of function.…”
Section: Discussionmentioning
confidence: 58%